Functional and bioactive properties of Bupleurum chinense DC. and Clematis chinensis osbeck mediated biogenic synthesized silver nanoparticles - Ter, Boon Siang; Sinouvassane Djearamane,; Yeoh, Fanne Fern Nii; Anto Cordelia Tanislaus Antony Dhanapal, (Universiti Kebangsaan Malaysia, 2022)
The synthesis of novel metallic nanoparticles (NPs) using plant materials has emerged as a cost-effective alternative to synthetic NPs and has found wide application in biomedical, cosmetic, bioremediation, and health care technology. This study aimed to synthesize and characterize the morphologies, functional groups, and crystalline structures of silver nanoparticles (AgNPs) deduced using B. chinense (Bc) and C. chinensis (Cc). The biogenic AgNPs were appraised for their antioxidant content, radical scavenging activities, antimicrobial, anti-inflammatory, and anti-diabetic activities to understand their functional and health promoting properties. The AgNPs deduced from both plants were spherical in shape with the size of 20-30 nm and possessed face centered cubic phase arrangement. The total phenolic content (TPC) was high in Cc-AgNPs (166.2100 mgGAE/g) and exhibited strong hydroxyl (OH-) and ABTS+ radical scavenging activities. On the contrary, Bc-AgNPs with higher TFC (286.1438 mgQE/g) had greater nitric-oxide (NO), DPPH, Fe2+scavenging and anti-albumin denaturation activities. Minimum anti-α-amylase activity disparity was observed between Cc-AgNPs (EC50 = 0.2903 mg/mL) and Bc-AgNPs (EC50 = 0.2975 mg/mL) due to various inhibition mode contributed by bioactive compounds. Besides, Bc-AgNPs showed strongest inhibition towards Gram negative bacteria while Cc-AgNPs was more effective as an antifungal agent. In conclusion, biogenic AgNPs exhibited strong functional and bioactive properties which may be attributed to the presence of bioactive compounds on the surface of AgNPs and further in-depth analysis are required to be used for various biomedical applications.